2003
DOI: 10.1016/s0022-5223(03)00355-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in morbidity and mortality during combined valve and coronary surgery

Abstract: Female gender is an independent risk factor for combined morbidity and mortality during and after combined valve and coronary bypass surgery. As with isolated coronary artery bypass grafting, women undergoing combined procedures have more premorbid conditions, are more often in heart failure, had an equal incidence of triple vessel disease but received fewer grafts than men, and, therefore, were more frequently incompletely revascularized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 20 publications
4
40
2
2
Order By: Relevance
“…In line with the majority of previous studies, we found distinctive risk profiles for men and women undergoing AVR 4, 6, 11, 12, 17, 27. Women undergoing AVR (isolated or combined) were older and had more nonatherosclerotic comorbid conditions at presentation including hypertension, diabetes mellitus, chronic obstructive pulmonary disease, atrial fibrillation/flutter, and anemia compared with men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the majority of previous studies, we found distinctive risk profiles for men and women undergoing AVR 4, 6, 11, 12, 17, 27. Women undergoing AVR (isolated or combined) were older and had more nonatherosclerotic comorbid conditions at presentation including hypertension, diabetes mellitus, chronic obstructive pulmonary disease, atrial fibrillation/flutter, and anemia compared with men.…”
Section: Discussionsupporting
confidence: 92%
“…The outcomes of AVR have improved significantly nationwide in the past decade 3. Several studies have assessed the differential impact of sex on outcomes of AVR but yielded conflicting results 4, 5, 6, 7, 8, 9, 10, 11, 12, 13. The interest in examining the sex gap in AS patients has been renewed with the introduction and widespread adoption of transcatheter AVR (TAVR).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates for CABG are documented to be approximately 3% [12,13], although it is well recognized that rates are higher for patients with significant comorbidities and patients receiving valvular or combined procedures [14,15]. Most recent studies have placed the incidence of stroke at about 4% for CABG, more than 7% for CABG/valve operations combined, and nearly 9% for mitral valve procedures [16].…”
Section: Commentmentioning
confidence: 99%
“…Of 297 treated subjects, 17 discontinued the study for consent withdrawal, 3 death, 5 or being lost to follow up. 9 The patient profiles are reviewed in Table 2.…”
Section: Resultsmentioning
confidence: 99%